Analysis Of The Effect Of Current Ratio, Total Asset Turnover, Debt To Equity Ratio, Net Profit Margin Toward Retrun on Equity - Muhamad Ardi Nupi Hasyim; Yayang Ayu Nuraeni (Yayasan Azka Hafidz Maulana, 2022)
This study was conducted to examine the effect of variables, Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Trunover (TAT), and Net Profit Margin (NPM) on Return on Equity (ROE). The research methodology as a sample uses proportional sampling with the criteria as (1) Manufacturing companies listed on the JSX that provide financial statements for the year ending December 31 during the 2005-2009 observation period, available at ICMD and annual reports. (2) The company must be registered at the beginning of the observation period and not delisted until the end of the observation period. (3) Financial statements include the value of financial ratios to be studied including ROE, CR, DER, TAT, and NPM. (4) At the beginning of the observation period until the end. A total of 51 samples were obtained from 205 companies during the five-year observation period in the manufacturing sector. There are 26 outliers who are lost due to extreme data. So the total sample is 229 during the five-year observation period. Data analysis with multiple linear regression from least square and hypothesis testing using partial t test, simultaneous F test at 5% significance level and adjusted R square test. Empirical evidence shows that CR, DER, TAT, and NPM have a positive influence. of ROE of manufacturing companies listed on the JSE during the period 2005-2009 at a significance level of 5% (each 0.000%). While the four independent variables CR, DER, TAT and NPM have an influence on ROE at the 5% significance level of 0.000%. Predictable of the four variables on ROE is 97.9% as shown by adjusted R square which is 97.